Bimodal distribution of Trypanosoma cruzi antibody levels in blood donors from a highly endemic area of Argentina: what is the significance of low‐reactive samples?. Issue 10 (27th May 2015) - Remesar, Mirta; Sabino, Ester C.; del Pozo, Ana; Mayer, Allen; Busch, Michael P.; Custer, Brian
<x xml:space="preserve">Abstract</x> BACKGROUND Low‐level seroreactive donor samples that are inconsistently detected by different Trypanosoma cruzi immunoassays are common, but the population distribution has not been reported in an endemic region. The objective was to understand the distribution of low‐level reactive samples using highly sensitive immunoassays and the relationship with epidemiologic evidence of exposure to T. cruzi. STUDY DESIGN AND METHODS Blood donors (BDs) were recruited in two blood banks located in Chaco province, in northeastern Argentina, from June 2006 to March 2007. Donors completed a Chagas exposure questionnaire and provided blood samples. All samples were tested in parallel with five contemporary and commercially available enzyme immunoassays for T. cruzi and a subgroup by a chemiluminescent assay. RESULTS Of the 1423 enrolled donors, 304 (21.4%) tested positive on all assays while 93 (6.5%) were reactive on at least one assay (inconclusive). Epidemiologic evidence of exposure to T. cruzi was significantly higher among positive and inconclusive donors compared to seronegative BD (p values range from 0.01 to <0.001 depending on the exposure). Histograms of the signal‐to‐cutoff values from all positive samples showed clear bimodal distributions for the whole parasite lysate assays, but not for the one recombinant antigen‐based assay. Low antibody level responses were present in 30% to 40% of the reactives, depending on the assay. CONCLUSION The population of individuals exposed to T. cruzi in highly endemic regions has a bimodal distribution of antibody response to the parasite. Although the clinical significance of low‐level reactivity is not fully established, these results may reflect evolving seroreversions after spontaneously resolved infections.